Assessment of Long-Term Badminton Experience on Foot Posture Index and Plantar Pressure Distribution - Ping Huang; Minjun Liang; Feng Ren (Applied Bionics and Biomechanics)
This study was aimed to analyze the foot posture index and plantar pressure characteristics of fifteen badminton players and fifteen controls. The hypothesis was that people with the habit of playing badminton would be significantly different with nonplaying people in foot posture index, 3D foot surface data, and plantar pressure distribution. Nine regions of plantar pressure were measured by using the EMED force platform, and badminton players showed significantly higher peak pressure in the hallux (p=0.003), medial heel (p=0.016), and lateral heel (p=0.021) and force-time integral in the hallux (p=0.002), medial heel (p=0.026), and lateral heel (p=0.015). There is no asymmetrical plantar pressure distribution between the left foot and the right foot of players. The mean foot posture index values of male and female badminton players are 5.2 ± 1.95 and 5.7 ± 1.15, respectively, and comparatively, those values of male and female controls are 1.5 ± 1.73 and 1.7 ± 4.16, respectively. This study shows that significant differences in morphology between people with the habit of playing badminton and people without that habit could be taken as a factor for a future study in locomotion biomechanics characteristics and foot shape of badminton players and in a footwear design in order to reduce injury risks.